Effects of agarwood at multiple stages of carcinogenesis: a systematic review - Hashim, Yumi Zuhanis Has-Yun; Samsudin, Nurhusna; Ab Ilah, Nazurah; Mohammad Tormizi, Ummu Athiyah; Mohd Nasir, Asmak Muti'ah; Zainudin, Nur Umisha (2019)
This systematic review sought to determine whether preclinical biological and mechanistic evidences of agarwood materials reported at multiple carcinogenic stages are significant to support plausibility of agarwood materials as potential therapeutics for cancer. Agarwood materials have been reported to have pre-clinical (in vitro and in vivo) evidences of anti-cancer effects in various types of cancer, however the diverse range of types of agarwood species and materials as well as carcinogenesis stage pose a challenge to discern the potential candidate or scheme for further work. More recent reports on agarwood toxicity further complicates the search for the potential therapeutics. Study selection criteria was determined based on framework outlined by the World Cancer Research Fund (WCRF) International/University of Bristol (UoB). In addition, care was taken to follow PRISMA reporting guidelines as closely as possible. Anti-cancer effect in the studies must be related to properties of antigenotoxic, apoptosis, antioxidant, cytotoxic, anti-inflammatory, anti- attachment, anti-spreading, anti-metastatic and anti-angiogenic. Papers that are published other than in English; review paper, comments and opinions; short paper (less than 6 pages), poster keynote and abstract; and papers published in 1900 and below are excluded. Search strategy was applied to selected electronic databases including Scopus, Springerlink, Taylor & Francis Online, Cambridge Core, Pub MEDLINE, Oxford Academic, Science Direct and Wiley Online Library. Number of 4473 studies were initially identified and 860 studies were included following screening. After removing duplicates, 112 papers were further analysed for eligibility. Presently, 47 studies judged eligible. Interim findings showed several characteristic trends where type of materials studied ranges from leaf, branch and essential oil; species studied are region/country specific but types of cancer studied are not research group-specific. Initial conclusion from the preclinical studies could be made where different species and types of agarwood material may have effects at multiple carcinogenesis stage in various types of cancer.